Pengaruh Ukuran Perusahaan dan Risiko Bisnis Terhadap Profitabilitas Serta Kebijakan Dividen - Epayanti, Ni Ketut Ayu; Yadnya, I Putu (E-Jurnal Manajemen, 2014)
Profitability is a key element that must be considered by a company with a high level of profitability is a reflection of the company can pay its obligations one of which pay dividends. Dividends are distributed depends on the decisions of each of the company's dividend policy. The purpose of this study was to determine the effect of firm size and business risk to the profitability and dividend policy at Manufacturing Company in Indonesia Stock Exchange. Sampling methods using purposive sampling then obtained a sample of 9 manufacturing companies. Data analysis techniques are used path analysis (path analysis). Based on the results of the analysis found that significant positive perpengaruh firm size on profitability, business risk significant positive effect on profitability, firm size kebijaka dividend significant positive, significant negative business risk on dividend policy, significant positive profitability on dividend policy.   Keywords: Company Size, Business Risk, Profitability, Dividend Policy
Keywords: Company Size, Business Risk, Profitability, Dividend Policy